Health conditions and the risk of home injury in French adults: results from a prospective study of the MAVIE cohort. Issue 2 (19th August 2021) - Rojas Castro, Madelyn Yiseth; Avalos, Marta; Contrand, Benjamin; Dupuy, Marion; Sztal-Kutas, Catherine; Orriols, Ludivine; Lagarde, Emmanuel
Abstract : Background: Home injury (HI) is a significant cause of mortality and morbidity in adults of all ages. Health conditions significantly impact HI among old adults, but little is known for other adults. Study design: Prospective cohort study. Objective: We assessed the associations between health-related factors and HI's risk in a French study, the MAVIE ( Mutualistes pour la recherche contre les Accidents de la VIE courante ) cohort. Methods: Poisson mixed models were fitted using health-related data information (diseases, treatments and disabilities) at baseline and the number of injuries prospectively recorded during the follow-up, adjusting for significant sociodemographics and exposure to a range of home activities. Attributable fractions were estimated based on risk ratio (RR) estimations measured in the fully adjusted models. Results: A total of 6146 dwelling adults aged 15 or older were followed up for 5.1 years on average. Vertigo or dizziness (RR=2.36, 95% CI 1.06 to 5.01) and sciatica or back pain (RR=1.49, 95% CI 1.08 to 2.05) were independently associated with an increased risk of HI. These two groups of conditions showed the most significant associations among people aged 15–49, whereas musculoskeletal diseases other than rachialgias and arthropathies were the most significant health-related risk factor in people aged 50 and older. Sciatica or back pain represented the highest burden of HIs in overall adults (8%) and among people aged 15–49 (12%). Conclusion: Our results suggest that adults with musculoskeletal disorders and vertigo or dizziness symptoms have a higher risk of HI, regardless of age.